Long-distance, short-distance: triathlon. One name: two ways - Santana-Cabrera, J.; Santana-Martin, F. J. (Procedia Engineering, 2015)
Triathlon is a relatively new sport. It is a multidisciplinary sport, which comprises three disciplines: swim, bike and run, as well as the two transition times between the swim and bike sections, and the bike and run sections. There are four common triathlon disciplines: Sprint-Distance, Olympic-Distance, considered Short-Distance (SD), Half Ironman and Ironman, Long-Distance (LD). The aim of this paper is to analyze whether there is a great difference in the way of winning a triathlon in both cases, SD and LD competitions. This paper will also analyze whether the winner of a triathlon is usually the best of one of the three disciplines and which discipline that is (swim, bike or run); the paper also examines the effect of the three disciplines on the overall result of the triathlon and which of the three disciplines is key to win the competition. This data is based on two events: the Volcano Triathlon (SD) and the Ironman Lanzarote (LD).